Joining of steel to aluminium and stainless steel to titanium for engineering applications - Rodrigues Pardal, Goncalo Nuno (Cranfield University, 2016)
Dissimilar welding has been subject of several investigations due to its potential importance in various industrial fields such as transportation, energy generation and management. Dissimilar welding can increase the design efficiency, by the use of complementary alloys with different properties, cost cutting and light weighting structures. The use of different materials within a component or structure to best suit a particular task, requirement or increase its life and performance has always been an ambition of several designers and engineers. This project investigated the joining steel and aluminium for the automotive industry and also stainless steel and titanium to be applied in the civil nuclear energy generation industry. These dissimilar metallic combinations are metallurgically incompatible and the formation of brittle intermetallic phases (IMC) need to be controlled or eliminated. To join steel to Al, laser spot welding process was selected, to avoid the bulk melting of steel and Al at the joint interface that enhance the formation of brittle IMC. This part of the work was focused in controlling the joining process to control the IMC formation of galvanized and uncoated steel to Al and verify if it was possible to have a sound and reliable joint in the presence of an IMC layer. In the second part of this study, stainless steel to titanium joining, a different approach was taken with the application of weld metal engineering to modify or eliminate the IMC formation. Several metals were evaluated as potential interlayers to use and laser welding with a Ni interlayer was evaluated with moderate success, due to the modified IMC with improved mechanical properties and the good compatibility between Ni and the stainless steel. A further improvement was achieved when Cu was brazed between stainless steel and Ti using CMT (Cold Metal Transfer) a low heat input MIG process. The final attempt was to use a different interlayer that was 3D printed and deposited in several layers. This interlayer was composed Cu and Nb that were selected as candidates to avoid the IMC formation between the stainless steel and Ti. With this approach it was possible to build an IMC free component and possibly improve and avoid IMC formation in several other dissimilar metallic combinations.
Keywords: Welding; Laser; GMAW; GTAW; Copper; Niobium